MATHEMATICAL MODELING OF MACHINE LEARNING ALGORITHMS («СОВРЕМЕННЫЕ ТЕХНОЛОГИИ КОМПЬЮТЕРНОЙ ЛИНГВИСТИКИ», 2024)
The article provides an overview of the main mathematical models in machine learning methods, such as linear regression, logistic regression, decision trees, support vector machine (SVM) and neural networks. The study highlights the importance of mathematical modeling for the development and application of machine learning algorithms and offers new perspectives in the field.